2011
DOI: 10.3357/asem.3016.2011
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Hormonal, Blood Lipid, and Hematological Profiles from a North Pole Expedition

Abstract: Although the expedition generated extreme physical stress, this was not directly reflected on hormonal recovery times as it was similar to other much less strenuous events. Despite important variations, all hormones returned to baseline values within 2 wk. Nonetheless, physical stress would appear to have more long-term effects on blood lipid and hematological profiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…These responses may also be due to central hypogonadism (Stroud et al 1997). Again, loss of body mass seems a common factor, with a 25% reduction observed (albeit in only two volunteers) in the data reported by Stroud (Stroud et al 1997), and a 10 kg loss reported by Gagnon (Gagnon et al 2011). …”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…These responses may also be due to central hypogonadism (Stroud et al 1997). Again, loss of body mass seems a common factor, with a 25% reduction observed (albeit in only two volunteers) in the data reported by Stroud (Stroud et al 1997), and a 10 kg loss reported by Gagnon (Gagnon et al 2011). …”
Section: Introductionmentioning
confidence: 53%
“…Consumption of the CCR facilitated maintenance of body mass and micronutrient status. Most studies investigating the physical responses to Polar expeditions have reported a decrease in body mass, with a concomitant reduction in circulating testosterone concentrations (Stroud et al 1997, Gagnon et al 2011, Johansen et al 1991) in a pattern consistent with central hypogonadism (Stroud et al 1997). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the influence of exercise on the sequestration of amino acids by the working muscle (Devlin et al., 1990), nutrient intake and/or progressive, exertion-linked changes in fuel selection may play a significant role in the sparing of amino acids that facilitate the maintenance of FFM (Burke, 2015). Macronutrient intake data were not available in this particular study, but similar expeditions have reported variable dietary intake of approximately ~35–66% carbohydrate, 29–55% fat, and 17–20% protein in ultra-athletes (Wolfe et al., 1984; Stroud et al, 1993, 1996; Gannon et al., 2001; Praz et al., 2015). We know from our own anecdotal observations during the 2015 and 2017 YAU that many of these athletes may consume more fat than described in earlier studies.…”
Section: Discussionmentioning
confidence: 91%
“…Participants in supported polar expeditions have traditionally experienced modest levels of negative energy availability 19 22 whilst those undertaking unsupported polar expeditions have experienced high levels of negative energy availability as evidenced by up to 25% loss of body weight 10 , 12 . Our previous work has suggested only modest levels of negative energy availability in participants in both the Spear-17 17 and Ice Maiden 18 expeditions.…”
Section: Introductionmentioning
confidence: 99%